Upaya Meningkatkan Omzet Penjualan Pada Usaha Mikro Kue Tradisional “Laris“ Di Menur Pumpungan Kota Surabaya - Kunto Inggit Gunawan; Mataji Mataji; Sigit Santoso (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
Since the implementation of the ASEAN Economic Community (AEC) at the end of 2015, it should encourage all economic actors, including SMEs and Micro Enterprises, to improve themselves in order to improve the quality of production of both goods and services. If this is not done, then Indonesia will be an "soft" market for other ASEAN countries because Indonesia has the largest population (population size) in ASEAN, namely no less than 270 million people. SMEs and Micro Enterprises, which are the embodiment of people's economic democracy, will be very hard hit if the heavy flow of goods and services from various ASEAN countries invades the Indonesian market. Realizing this, strengthening (empowering) SMEs and Micro Enterprises is a necessity and necessity to be able to find a national identity that has comparative advantage and competitive advantage. This activity begins with identifying existing problems and then finding a method for solving them. The method used is by providing training and mentoring. The results that have been achieved are the ability of the Traditional Cake business to optimize its sales by using local raw materials. In this way, the "best-selling" Traditional Cake Micro Business can improve its capabilities in the fields of production and business management and online marketing via social media. These outcomes are an indication of increased business empowerment.